Triglyceride glucose-weight-adjusted waist index as a cardiovascular mortality predictor: incremental value beyond the establishment of TyG-related indices - Jiajun Qiu; Jin’e Li; Shan Xu; Jingqi Yang; Haixia Zeng; Yuying Zhang; Shiqi Yang; Lixuan Fang; Jiadian Huang; Hongtao Zhou; Jiaying Feng; Yujie Zan; et al. (Cardiovascular Diabetology)
Abstract Background Cardiovascular disease (CVD) remains the leading cause of mortality worldwide, emphasizing the need for enhanced risk stratification tools. The triglyceride‒glucose-weight adjusted waist index (TyG-WWI), which integrates insulin resistance and central obesity, has emerged as a potential predictor, but its performance relative to traditional TyG-related indices (TyG, TyG-WC, TyG-WHtR) requires further validation. Methods We analyzed data from 24,255 participants in the National Health and Nutrition Examination Survey (NHANES, 1999–2018). Weighted Cox proportional hazards models were used to assess the associations between TyG-related indices and cardiovascular mortality. Restricted cubic splines (RCSs) with four knots were employed to explore dose‒response relationships. Traditional and time-dependent receiver operating characteristic (ROC) analyses, net reclassification improvement (NRI) analyses, and subgroup and sensitivity analyses were conducted to evaluate predictive performance and robustness. Results Over a median follow-up of 9.67 years, 854 cardiovascular deaths were recorded. According to the fully adjusted models, each increase in the standard deviation of the TyG-WWI was associated with a 45% greater risk of cardiovascular mortality (HR = 1.45, 95% CI 1.31–1.60), which was stronger than the associations observed for TyG (HR = 1.24, 95% CI 1.12–1.38), TyG-WC (HR = 1.39, 95% CI 1.27–1.53), and TyG-WHtR (HR = 1.43, 95% CI 1.30–1.58). When stratified by quartiles, the TyG-WWI exhibited a clear dose‒response relationship. RCS analyses revealed that the TyG-WWI had a linear association with cardiovascular mortality (P-nonlinear = 0.491), whereas the TyG index exhibited a U-shaped association, and the TyG-WC index and TyG-WHtR showed L-shaped associations (all P-nonlinear < 0.05). Traditional ROC analysis revealed that the TyG-WWI had the highest AUC (0.694, 95% CI 0.678–0.710). Time-dependent ROC analyses demonstrated that the AUC for the TyG-WWI ranged from 0.706 to 0.751 across different follow-up time points, which was consistently greater than those of the other TyG-related indices. NRI analyses indicated significant improvements in risk reclassification when the TyG-WWI was used compared with traditional TyG-related indices (10.4% vs. TyG, 9.4% vs. TyG-WC, 9.1% vs. TyG-WHtR). Subgroup analyses revealed stronger associations in younger adults (≤ 60 years, HR = 2.03, 95% CI 1.78–2.32). Conclusion The current study is the first to validate that the TyG-WWI is a reliable risk prediction tool for cardiovascular death in the general population and has greater predictive value than traditional TyG-related parameters. The results support its potential as a supplementary tool among TyG-derived markers for assessing cardiovascular death.